The Wage Earnings Impact of Historically Black Colleges and Universities. - Mykerezi, Elton; Milis, Bradford F. (Southern Economic Journal, 2008)
The impact on wages from blacks' attendance of historically black colleges and universities (HBCUs) versus other colleges is examined using geo-coded National Longitudinal Survey of Youth 1979 data. The paper reconciles seemingly conflicting findings in previous studies by estimating wage profiles over time, rather than by estimating wages at a single point in time. Estimates indicate that black males show no initial wage advantage as a result of HBCU attendance, but their wages increase 1.4-1.5% faster per year after attending HBCUs compared to other colleges. This faster growth generates discounted career earnings from HBCU attendance that are 9.6% higher for HBCU attendees and 8.9% higher for the average four-year college black student. For black females, HBCU attendance has no significant impact on initial wages or on subsequent wage growth.